Will protection of 17% of land by 2020 be enough to safeguard biodiversity and critical ecosystem services?. Issue 1 (January 2015) - Larsen, Frank W.; Turner, Will R.; Mittermeier, Russell A.
Abstract To stem the loss of biodiversity and ensure continued provision of essential ecosystem services world leaders adopted the 20 Aichi Biodiversity Targets in 2010, to be fulfilled by 2020. One key target (Target 11) prescribes an expansion of the global protected area system to at least 17% of land surface and 10% of oceans by 2020. Given that these targets are predominantly based on political feasibility rather than scientific evidence, it remains unclear whether fulfilment of Target 11 will suffice to safeguard biodiversity and ensure continued provision of essential ecosystem services. Despite many data gaps, in particular for ecosystem services, we can use existing global data to estimate the required protected area on land for biodiversity (a minimum of c. 17%) and biomass carbon storage (a minimum of c. 7–14% additional area to protect 75–90% of the unprotected carbon stock), which illustrates that the target of 17% of land will probably fall short in meeting these goals. As crossing thresholds or tipping points in ecosystems could trigger non-linear, abrupt change in delivery of ecosystem services, we need a science-driven understanding of how much protected, intact nature is needed to avoid unforeseen transgression of planetary boundaries.